2022
DOI: 10.3390/app12031049
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Factor Rear-End Collision Avoidance in Connected Autonomous Vehicles

Abstract: According to World Health Organization (WHO), the leading cause of fatalities and injuries is rear-ending collision in vehicles. The critical challenge of the technologically rich transportation system is to reduce the chances of accidents between vehicles. For this purpose, it is especially important to analyze the factors that are the cause of accidents. Based on these factors’ results, this paper presents a driver assistance system for collision avoidance. There are many factors involved in collisions in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…In this context, the probability of death occurring on the road is higher in secondary traffic accidents than in primary ones, making it crucial to quickly identify accidents on the road to prevent subsequent secondary accidents. Consequently, in the field of artificial intelligence, technologies are being actively developed to quickly detect traffic accidents or accurately classify types of accidents [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the probability of death occurring on the road is higher in secondary traffic accidents than in primary ones, making it crucial to quickly identify accidents on the road to prevent subsequent secondary accidents. Consequently, in the field of artificial intelligence, technologies are being actively developed to quickly detect traffic accidents or accurately classify types of accidents [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…This is all the more true given that Kalra and Paddock [6] have demonstrated that the validation of AV by driving would require covering billions of kilometers. The use of simulation has many advantages, including testing controllability and path planning strategies, simulating different ranges of operational parameters, ensuring reproducibility and efficiency of the tests [7,8], testing specific collision avoidance strategies [9], etc. Previous authors have worked on the validation of automotive models and propose an assessment process that is not only focused on safety validation, but also on the quantification of modeling errors and uncertainties of the simulation compared to real driving [10].…”
Section: Introductionmentioning
confidence: 99%